Advancement in Veterinary Surgical Research and Imaging Techniques - Singh, Kiranjeet; Gopinathan, Aswathy (Indian Farming, 2015)
The Division of Veterinary Surgery at IVRI has contributedsignificantly towards the development of effective and userfriendlysurgical techniques for animals, especially in the areas of orthopaedic surgery, anaesthesia and pain management, biomaterial research, radiology and imaging techniques, laproscopic surgery, urolithiasis and stem cell therapy.